Editorial Note: Welcome to Volume 21 and the year 2018 - Assounga, Alain G (African Journal of Nephrology, 2018)
African Journal of Nephrology (AJN) has completed a full year of operation as a web-based journal. After addressing a few teething problems, the journal is now running smoothly. I wish to thank reviewers, readers and the members of the editorial board for having participated in this endeavour. On behalf of the editorial board, I wish to thank all colleagues who have chosen to submit their valuable work to our journal. A special welcome and thanks to contributors who have submitted their manuscript in French, with an English abstract. They ensure that AJN remains a representative vehicle for nephrology research output in Africa. Volume 20, for the year 2017, has now given way to Volume 21, which will include publications throughout the year 2018. As a tribute, I wish to summarize few highlights of Volume 20. The story of the African Association of Nephrology (AFRAN) by Prof Rashad Barsoum, the founding president of AFRAN, is a very good record of the development of nephrology in Africa. The review of renal physiology in patients with potassium disorders by Prof Mitch Halperin and the review of focal and segmental glomerulosclerosis by Prof John Feehally are excellent updates of the two topics. Original articles and case reports from contributors from various African regions are testament to the active production of nephrology knowledge in Africa. Finally, congress proceedings of the AFRAN Congress in March 2017 in Yaoundé (Cameroon) and of the Southern African Transplantation Society Congress in September 2017 in Durban (South Africa) are excellent records of high quality nephrology meetings in Africa. As we are continuing to digitize and preserve our past, I wish to invite everyone to read our archive of publications. I urge everyone who may have copies of old AJN issues or manuscripts that are missing in the archive, to forward them to us to ensure that we make all our past papers available online. In the beginning, AJN started as a newsletter, published by the late Prof Salma Suleiman of Sudan. To complete the AJN archive, we hope to include the past newsletters as a tribute to the late Prof Suleiman. We urge anyone having any copies of the newsletter to forward it to AJN. As in Volume 20 in 2017, Volume 21 will consist of a single issue and include all publications for 2018. They will be added throughout the year as they are accepted for publication. We should expect exciting reviews by experts as in our previous volumes as well as special articles. For our legacy project that was started by Prof Rashad Barsoum, first AFRAN President, we will request the subsequent AFRAN presidents to each submit a review of the period of their tenure. As in the past, we expect to publish original articles as well as interesting case reports, and we encourage regional and national societies to submit the abstracts from their conference proceedings for publication. Finally, I wish to take this opportunity to express my best wishes for the year 2018 to all contributors, reviewers and readers. Alain G Assounga Editor-in-Chief